Hubungan Self-Efficacy dengan Mekanisme Koping pada Penderita Diabetes Melitus Tipe 2 di Kelurahan Selabatu Wilayah Kerja UPTD Puskesmas Selabatu Kota Sukabumi - Pramudita, Kirana; Dewi, Rosliana; Budhiana3, Johan (Jurnal Ragam Pengabdian, 2026)
Diabetes mellitus is a chronic condition characterized by persistently elevated blood glucose levels. This study aims to determine the relationship and strength of the association between self-efficacy and coping mechanisms among patients with Type II Diabetes Mellitus in the Selabatu Subdistrict, within the service area of the Selabatu Community Health Center (UPTD Puskesmas) in Sukabumi City. This research utilized a quantitative correlational design using a cross-sectional method. The research group included 165 people, with a sample of 117 participants chosen through proportional random sampling. Data were collected using the Diabetes Management Self-Efficacy Scale to measure self-efficacy and the Brief Cope Inventory to measure coping mechanisms. Data analysis was performed using the Chi-square test with a contingency coefficient at a 5% significance level. The results showed that the majority of respondents had high self-efficacy (72.5%) and maladaptive coping mechanisms (68.4%). Statistical analysis revealed a significant association between self-efficacy and coping mechanisms (p < 0.000) with a strong correlation (CC = 0.509). In conclusion, there is a strong correlation between self-efficacy and coping mechanisms in patients with Type II Diabetes Mellitus. Enhancing adaptive coping strategies is crucial for improving self-efficacy